Global and temporal variations in hydrocarbons and nitriles in Titan's stratosphere for northern winter observed by Cassini/CIRS - Teanby, N; Irwin, P; de Kok, R; Nixon, C; Coustenis, A; Royer, E; Calcutt, S; Bowles, N; Fletcher, L; Howett, C; Taylor, F (2008)
Mid-infrared spectra measured by Cassini's Composite InfraRed Spectrometer (CIRS) between July 2004 and January 2007 (Ls = 293 ° - 328 °) have been used to determine stratospheric temperature and abundances of C2H2, C3H4, C4H2, HCN, and HC3N. Over 65,000 nadir spectra with spectral resolutions of 0.5 and 2.5 cm-1 were used to probe spatial and temporal composition variations in Titan's stratosphere. Cassini's 180° orbital transfer in mid-2006 allowed low emission angle observations of the north polar region for the first time in the mission and allowed us to probe the full latitude range. We present the first measurements of composition variations within the polar vortex, which display increasing abundances right up to 90° N. The lack of a homogeneous abundance-latitude variation within the vortex indicates limited horizontal mixing and suggests that subsidence is greatest at the vortex core. Contrary to numerical model predictions and tropospheric cloud observations, we do not see any evidence for a secondary circulation cell near the south pole, which suggests a single Hadley-type circulation in the stratosphere at this epoch. This difference can be reconciled if the secondary cell is restricted to altitudes below 100 km, where there is no sensitivity in our data. Temporal variations in composition were observed in the south, with volatile species becoming less abundant as the season progressed. The observed variations are compared to numerical model predictions and observations from Voyager. © 2007 Elsevier Inc. All rights reserved.